Artificial Intelligence Systems in Managing Human Resources: An Exploratory Study in the Indian Context - Shambhavi Pandey (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper is an attempt to examine the factors affecting the use of Artificial Intelligence (AI) by human resource professionals with their ‘professional experience (in years)’ as a moderating variable. A survey research conducted on a sample of 123 senior human resource professionals. The key findings reveal that the use of AI would lead to a lack of employee productivity, morale and trust. It further illustrates that AI would have adverse consequences on growing employee silence and data manipulations. HR practitioners in India in are differing in adopting AI is not because of their fear of losing their jobs but because of the sheer nature of unpredictable outcomes and lack of strong legislations on using AI. This study answers the question of why there is not a widespread use of artificial intelligence systems in India for managing human resources even though AI is being used for other domains of management.